Self-Gated Fat-Suppressed Cardiac Cine MRI - Ingle, R. Reeve (Magn Reson Med, 2014)
PURPOSE: To develop a self-gated alternating repetition time balanced steady-state free precession (ATR-SSFP) pulse sequence for fat-suppressed cardiac cine imaging. METHODS: Cardiac gating is computed retrospectively using acquired MR self-gating data, enabling cine imaging without the need for electrocardiogram (ECG) gating. Modification of the slice-select rephasing gradients of an ATR-SSFP sequence enables the acquisition of a 1D self-gating readout during the unused short repetition time (TR). Self-gating readouts are acquired during every TR of segmented, breath-held cardiac scans. A template-matching algorithm is designed to compute cardiac trigger points from the self-gating signals, and these trigger points are used for retrospective cine reconstruction. The proposed approach is compared with ECG-gated ATR-SSFP and balanced steady-state free precession (bSSFP) in ten volunteers and five patients. RESULTS: The difference of ECG and self-gating trigger times has a variability of 13 ± 11 ms (mean ± SD). Qualitative reviewer scoring and ranking indicate no statistically significant differences (P > 0.05) between self-gated and ECG-gated ATR-SSFP images. Quantitative blood-myocardial border sharpness is not significantly different among self-gated ATR-SSFP (0.61 ± 0.15 mm(−1)), ECG-gated ATR-SSFP (0.61 ± 0.15 mm(−1)), or conventional ECG-gated bSSFP cine MRI (0.59 ± 0.15 mm(−1)). CONCLUSION: The proposed self-gated ATR-SSFP sequence enables fat-suppressed cardiac cine imaging at 1.5 T without the need for ECG gating and without decreasing the imaging efficiency of ATR-SSFP.